A Brief Report of West Nile Virus Neuroinvasive Disease in the Summer of 2012 in Hamilton, Ontario - Lei Jiao; Cheryl Main (Canadian Journal of Infectious Diseases and Medical Microbiology)
West Nile neuroinvasive disease is a severe infectious disease that is associated with a high mortality rate, especially in immunocompromised hosts. Physicians who are aware of its clinical presentations may be able to order diagnostic tests more appropriately and avoid inappropriate treatment. In the present series, the cases of seven patients admitted to Hamilton Health Sciences (Hamilton, Ontario) in the summer of 2012 with a diagnosis of West Nile neuroinvasive disease were retrospectively reviewed based on available medical records. According to the clinical and laboratory criteria published by the Centers for Disease Control and Prevention, five cases were diagnosed as encephalitis, one case as meningitis and one case as meningomyelitis. Patients were managed supportively. Forty-three percent (three of seven) presented with rash, 71% (five of seven) did not report headache despite exhibiting neurological symptoms, 43% (three of seven) did not have fever on presentation and 37.5% of cerebrospinal fluid samples exhibited a neutrophil predominance. The mortality rate in the present series was 14.3% (one of seven), and 57.1% (four of seven) of the patients had residual symptoms on discharge and at follow-up.